2022
DOI: 10.1186/s12884-022-04911-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 status and folic acid/vitamin B12 related to the risk of gestational diabetes mellitus in pregnancy: a systematic review and meta-analysis of observational studies

Abstract: Background This review was conducted to investigate the association between serum vitamin B12 levels as well as folic acid/vitamin B12 during pregnancy and the risk of gestational diabetes mellitus (GDM). Methods A comprehensive search of electronic databases (Embase, PubMed, and Web of Science) was performed. The odds ratios (ORs) with 95% confidence intervals (CIs) of GDM risk were summarized using a random effects model. We also performed subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Unbalances in serum vitamin B12 and folic acid (folic acid and vitamin B12) are more strongly linked to gestational diabetes mellitus. Folic acid is a crucial vitamin during pregnancy since it plays a role in DNA methylation and the manufacture of proteins and nucleic acids needed for cell replication and embryonic growth [ 17 ]. A safe and viable strategy that may provide pregnant women exposed to free radicals with a way to reduce the risk of foetal growth decline is higher-dose folic acid supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…Unbalances in serum vitamin B12 and folic acid (folic acid and vitamin B12) are more strongly linked to gestational diabetes mellitus. Folic acid is a crucial vitamin during pregnancy since it plays a role in DNA methylation and the manufacture of proteins and nucleic acids needed for cell replication and embryonic growth [ 17 ]. A safe and viable strategy that may provide pregnant women exposed to free radicals with a way to reduce the risk of foetal growth decline is higher-dose folic acid supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is essential to acknowledge certain limitations of this study. First, it has been reported that vitamin B 12 and folate act as cofactors in regulating HCY levels, and vitamin B 12 deficiency has been associated with GDM 48 . Unfortunately, due to limitations in LC‐MS/MS technology, we were unable to measure vitamin B 12 .…”
Section: Discussionmentioning
confidence: 98%
“…First, it has been reported that vitamin B 12 and folate act as cofactors in regulating HCY levels, and vitamin B 12 deficiency has been associated with GDM. 48 Unfortunately, due to limitations in LC-…”
Section: Discussionmentioning
confidence: 99%
“…The population studied had a high prevalence of vitamin D insufficiency, but the lack of an observed difference might have been related to the multiple-micronutrient format or the timing of the intervention [ 42 ]. B-group vitamins have also been related with maternal glycaemia [ 11 , 17 , 18 , 43 ], with maternal vitamin B12 deficiency associated with increased insulin resistance and adiposity among offspring [ 9 , 13 , 44 ]. Thus, the beneficial effects of supplementation on infant weight gain among our cohort could be related to improvements in nutritional sufficiency, though the mechanisms are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Several micronutrients have been related to offspring adiposity, for example, increased adiposity has been observed among offspring whose mothers were vitamin D deficient during pregnancy [ 8 , 12 , 14 ]. Likewise, B-vitamin deficiencies have been observed among mothers with diabetes [ 10 , 11 , 17 , 18 ], which may contribute to increased offspring adiposity [ 9 , 13 ]. Similarly, myo -inositol, a non-essential sugar alcohol involved in regulating glucose and lipid metabolism, has been postulated to counteract the effects of maternal dysglycaemia and dyslipidaemia on offspring adiposity [ 19 ], and probiotics have been proposed as beneficial in preventing gestational dysglycemia [ 20 ].…”
Section: Introductionmentioning
confidence: 99%